CD14+ peripheral blood mononuclear cells from chronic myeloid leukemia and normal donors are inhibitory to short- and long-term cultured colony-forming cells - Heissig, Beate; Pasternak, Günter; Hörner, Susanne; Schwerdtfeger, Rainer; Rossol, Siegfried; Hehlmann, Rüdiger (Leukemia research, 2000)
Monocyte-induced cell-cytotoxicity has been implicated in the mechanism of suppression of normal haematopoietic progenitors in chronic myeloid leukemia (CML). We examined here the in vitro effect of CML-derived and normal peripheral blood (PB) monocytes on short- and long-term cultured haematopoietic progenitor cells. Short-term coculture (5 days) of CML or normal monocytes with CML or normal peripheral blood mononuclear cells (PBMNC)/CD34+ cells as targets resulted in a significant inhibition of colony-forming cell (CFC) growth. Coculture conditioned medium (CCM) from 5-days cocultures of normal or CML CD14+ monocytes with CD34+ cells were likewise inhibitory to CFC. In 5-week long-term cocultures of monocytes in direct contact with normal bone marrow (BM) progenitors, CML monocytes reduced the proportion of long-term cultured CFC (LTC-CFC) significantly to 52% of the controls, while normal monocytes had a less pronounced inhibitory effect (89% of the controls) on LTC-CFC. Reduction of LTC-CFC was great when CML monocytes and target cells were separated by a transwell membrane as compared to control cultures in the absence of CD14+ cells (53.5 vs. 9%). CCM from 5-week cocultures of normal or CML CD14+ monocytes with CD34+ progenitors from bone marrow (BM) cells were also inhibitory to CFC. No difference in cytokine levels for TNF-α, IFN-γ, G-CSF, IL-10, IL-6 was detectable between CML CD14+ CCM and control CCM derived from short- and long-term cocultures. Our results suggest that CML monocytes may play a role in the inhibition of normal haematopoiesis through a yet not defined soluble factor supporting the expansion of the malignant clone in CML.
Gesehen am 19.05.2022
Im Titel ist das Pluszeichen hochgestellt